Analisis Varians Anggaran Operasional dan Realisasinya dalam Penilaian Kinerja Perusahaan: Studi Kasus PT. Matahari Sinar Panbersi - Dewi Clarita; Evi Marlina; Annie Mustika Putri (AKUNTANSI 45, 2024)
This research aims to determine the procedures for preparing and implementing operational budgets and analyzing the level of effectiveness of operational budget management at PT. Matahari Sinar Panbersi for the period 2020 to 2022 and whether the implementation of the operational budget has been effective in it. The type of research used in this research is quantitative research using descriptive methods. Data collection techniques were carried out using interviews and documentation. This research data is the result of observations in the field, through interviews and presentation of data from PT. Matahari Sinar Panbersi. The theory used to determine and analyze the effectiveness of operational budget management is variance analysis and calculation of effectiveness levels. Based on the research results, it shows that the preparation and implementation process uses the bottom up method, in the analysis of cost variances and their realization it shows that it is unfavorable, but in terms of the level and criteria for the effectiveness of operational budget management at PT. Matahari Sinar Panbersi from 2020 to 2022 falls into the very effective criteria.